Clinical presentation and outcomes in children with retinoblastoma managed at the Uganda Cancer Institute. (8th March 2022) - Kalinaki, Abubakar; Muwonge, Haruna; Balagadde-Kambugu, Joyce; Mulumba, Yusuf; Ntende, Jacob; Ssali, Grace; Nakiyingi, Lydia; Nakanjako, Damalie; Nalukenge, Caroline; Ampaire, Anne M.
Abstract : Background . The majority of patients with retinoblastoma, the most common intraocular cancer of childhood, are found in low-and middle-income countries (LMICs), with leukocoria being the most common initial presenting sign and indication for referral. Findings from the current study serve to augment earlier findings on the clinical presentation and outcomes of children with retinoblastoma in Uganda. Methods. This was a retrospective study in which we reviewed records of children admitted with a diagnosis of retinoblastoma at the Uganda Cancer Institute from January 2009 to February 2020. From the electronic database, using admission numbers, files were retrieved. Patient information was recorded in a data extraction tool. Results . A total of 90 retinoblastoma patients were studied, with a mean age at the first Uganda Cancer Institute (UCI) presentation of 36.7 months. There were more males (57.8%) than females, with a male to female ratio of 1.37 : 1. The majority (54.4%) had retinoblastoma treatment prior to UCI admission. The most common presenting symptoms were leukocoria (85.6%), eye reddening (64.4%), and eye swelling (63.3%). At 3 years of follow-up after index admission at UCI, 36.7% of the patients had died, 41.1% were alive, and 22.2% had been lost to follow-up. The median 3-year survival for children with retinoblastoma in our study was 2.18 years. Significant predictors of survival in the multivariate analysis were follow-up duration (P ̲ < 0.001 ), features of metastatic spread (P = 0.001 ), history of eye swelling (P = 0.012 ), and bilateral enucleation (P = 0.011 ). Conclusions . The majority of children who presented to the Uganda Cancer Institute were referred with advanced retinoblastoma, and there was a high mortality rate. Retinoblastoma management requires a multidisciplinary team that should include paediatric ophthalmologists, paediatric oncologists, ocular oncologists, radiation oncologists, and nurses.